Oxytocin modulates meta-mood as a function of age and sex - Ebner, Natalie; Horta, Marilyn; Lin, Tian; Fischer, Håkan; Cohen, Ronald; Feifel, David (Frontiers in Aging Neuroscience, 2015)
Attending to and understanding one’s own feelings are components of meta-mood and constitute important socio-affective skills across the entire lifespan. Growing evidence suggests a neuromodulatory role of the neuropeptide oxytocin on various socio-affective processes. Going beyond previous work that almost exclusively examined young men and perceptions of emotions in others, the current study investigated effects of intranasal oxytocin on meta-mood in young and older men and women. In a double-blind between-group design, participants were randomly assigned to self-administer either intranasal oxytocin or a placebo before responding to items from the Trait Meta-Mood Scale about attention to feelings and clarity of feelings. In contrast to older women, oxytocin relative to placebo increased attention to feelings in older men. Oxytocin relative to placebo enhanced meta-mood in young female participants but reduced it in older female participants. This pattern of findings supports an age- and sex-differential modulatory function of the neuropeptide oxytocin on meta-mood, possibly associated with neurobiological differences with age and sex.